Evaluation of an aminobisphosphonate (alendronate) in the management of periodontal osseous defects - Veena H; Prasad Deepak (Journal of Indian Society of Periodontology, 2010)
Background and Objectives: Alendronate, an aminobisphosphonate, is capable of inhibiting periodontitis associated osteoclastic activity and hence is effective in protecting the alveolar bone in periodontitis. In the present study, we explored the efficacy of local delivery of alendronate on the alveolar bone following mucoperiosteal flap surgery. This is the first study to use polymer impregnated gel based delivery of alendronate. Materials and Methods: A total of 15 patients with chronic periodontitis in the age group of 35 - 55 years, of both sexes, with pocket depth of ≥ 5mm and radiographic evidence of identical osseous defects in the mandibular molar region bilaterally were included in this prospective study. A gel based drug delivery system of Alendronate was formulated. Following surgical flap debridement, 0.1 ml alendronate gel and 0.1 ml placebo gel was placed at the experimental and control sites respectively. Clinical and radiographic parameters were recorded at baseline, three months and six months post surgery. Results: Alendronate was more effective in improving clinical and radiographic parameters compared to placebo. Interpretation and Conclusion: Alendronate is effective in the management of periodontitis associated bone loss. Gel based local delivery of the drug addresses the critical concern of exposing the patient to adverse effects of systemic administration.